Electrospun polysuccinimide scaffolds containing different salts as potential wound dressing material - Pálos, Veronika; Nagy, Krisztina S.; Pázmány, Rita; Juriga-Tóth, Krisztina; Budavári, Bálint; Domokos, Judit; Szabó, Dóra; Zsembery, Ákos; Jedlovszky-Hajdu, Angela (Beilstein Journal of Nanotechnology, 2024)
In this research, we applied electrospinning to create a two-component biodegradable polymeric scaffold containing polysuccinimide (PSI) and antibacterial salts. Antibacterial agents for therapeutical purposes mostly contain silver ions which are associated with high environmental impact and, in some cases, may cause undesired immune reactions. In our work, we prepared nanofibrous systems containing antibacterial and tissue-regenerating salts of zinc acetate or strontium nitrate in different concentrations, whose structures may be suitable for developing biomedical wound dressing systems in the future. Several experiments have been conducted to optimize the physicochemical, mechanical, and biological properties of the scaffolds developed for application as wound dressings. The scaffold systems obtained by PSI synthesis, salt addition, and fiber formation were first investigated by scanning electron microscopy. In almost all cases, different salts caused a decrease in the fiber diameter of PSI polymer-based systems (<500 nm). Fourier-transform infrared spectroscopy was applied to verify the presence of salts in the scaffolds and to determine the interaction between the salt and the polymer. Another analysis, energy-dispersive X-ray spectroscopy, was carried out to determine strontium and zinc atoms in the scaffolds. Our result showed that the salts influence the mechanical properties of the polymer scaffold, both in terms of specific load capacity and relative elongation values. According to the dissolution experiments, the whole amount of strontium nitrate was dissolved from the scaffold in 8 h; however, only 50% of the zinc acetate was dissolved. In addition, antibacterial activity tests were performed with four different bacterial strains relevant to skin surface injuries, leading to the appearance of inhibition zones around the scaffold discs in most cases. We also investigated the potential cytotoxicity of the scaffolds on human tumorous and healthy cells. Except for the ones containing zinc acetate salt, the scaffolds are not cytotoxic to either tumor or healthy cells.
Keywords: antibacterial activity; electrospinning; polysuccinimide; scaffold; wound dressing